Utilization of YouTube Social Communication Networking in Establishing Indonesian Street Food Opinion - Lidya Wati Evelina; Yulianne Safitri (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
In the development of technology in the era of society 5.0, the trend of community activity in social media is oriented towards conversations about YouTube content. The urgency of this research is expected to contribute to the development of communication science, especially for social media activists, especially Indonesian YouTubers, to create Indonesian Street Food content by seeing the phenomenon of foreign YouTubers liking and creating Indonesian Street food content on their YouTubers channel. Discussion on Networking in Establishing The opinion of Indonesian street food that is reviewed on YouTube social media aims to explain foreigner reviews about Indonesian street food from the conversations that occur in the comments. The theory used is the theory of social communication networks, the concept of online community involvement, creative content on YouTube using a qualitative approach. Data collection was carried out using the netnography method obtained from observing content and comments on the YouTube Channel. The findings of this study are that there is intense and funny communication between foreigners regarding terms used in street food in Indonesia, likes and comments on YouTube channels can provide recommendations for foreign tourists to choose Indonesian Street Food when visiting Indonesia. The results of his research opinion were formed from conversations that took place through comments on Indonesian street food content on Luke Martin and Sabrina Davidson's Foreigners YouTube Channel.